Effects of nitrogen treatments and bacterial inoculation on macro- and micro-element contents of the Halisbey peanut variety - Aşik, Ferrin Ferda (Italian Journal of Agronomy, 2023)
This study was conducted to determine the effect of nitrogen (N) doses (0, 40, 80, 120, 160, 200, and 240 kg ha-1) and bacterial inoculation on macro- (N, P, K, Ca, Mg, and Na) and micro- (Fe, Cu, Zn, Mn, and B) element contents of the Halisbey peanut variety. The nutrient requirements, specific nutrient management strategies, and adaptation of the variety to the regions where it was grown were also assessed. According to the average results of the N applications, different doses affected the levels of N (240N+B: 1.76%) alongside the content of other macro-elements, as well as sodium (200N: 0.09 mg kg-1), iron (80N: 32.39 mg kg-1), and copper (40N: 14.11 mg kg-1) among the micro-elements. The bacterial application was not found to significantly increase N content (240N+B: 1.76%), calcium content (0.08%) and zinc content (49.68 mg kg-1). At the same time, (240N+B) bacteria and N application increased the N ratio.